Das Trainingsalter - ein neuer Risikofaktor akuter Badmintonverletzungen - Kluger, R.; Stiegler,H.; Engel, A. (Sportverletzung Sportschaden, 1999)
The incidence of badminton injuries is low compared with other sports, but acute injuries are generally more severe. Little is known about the risk of competitive badminton players to get an acute badminton injury. The purpose of this study was to define for the first time "years of playing badminton on a competitive level" as a risk factor for acute badminton injuries. 179 badminton injuries of 102 Austrian competitive badminton players, some of them being elite players in the european championships, were retrospectively registered. The years 1993, 1994 and 1995 were covered by our investigation. Injury incidences were defined as injuries/1000 h and were calculated separately for the 0. through the 21st year of competitive badminton. The incidence of acute badminton injuries increased constantly from the 0 to the 7th year of competitive badminton. The 6th and 7th year of competitive badminton showed a threefold increased incidence of acute badminton injuries when compared with the first year and the late years of the career as a competitive badminton player. We found no correlation between the incidence of acute badminton injuries and age, gender, hours played per year or time of warming up. We conclude that players being engaged in competitive badminton for 5 to 8 years represent a high risk population for acute badminton injuries. In contrast players at the beginning and towards the end of the competitive career showed a markedly lower risk for acute badminton injuries. We recommend additional training efforts concerning technical skills and endurance as well as proper rehabilitation of sports injuries for the high risk group of badminton players.